Some questions of ethics in randomized controlled trials - Khera, Reetika (Review of development economics, 2024)
Questions of ethics in randomized controlled trials (RCTs) in development economics need greater attention and a wider perspective. RCTs are meant to be governed by the three principles laid out in the Belmont Report, but often violated them, for example, when local laws are flouted. In other cases, the framework of the Belmont Report itself has proved inadequate: for instance, when there are unintended outcomes or adverse events for which no‐one is held accountable. Primarily using RCTs conducted in India, this paper highlights eight areas of concern. RCTs also have a disproportionate influence on shaping research agendas and on policy. Though ethical issues have been raised, there has been little engagement from the RCT community—a manifestation of its power in the profession. As current safeguards (such as oversight by Institutional Review Boards) have failed to protect human subjects, the concluding section discusses possible ways to resolve these issues.